Teachers’ Learning Agility: A Catalyst For Creating Learning Transformation In Early Childhood Education After The Covid-19 Pandemic - Handayani, Dewa Ayu Puteri; Ambara, Didith Pramunditya (Universitas Nahdlatul Ulama Surabaya, 2023)
Teachers are faced with numerous difficulties during the COVID-19 Pandemic, particularly in ensuring that the learning process continues to run smoothly in the face of uncertainty. The aim of this study was to examine the relationship between learning agility and commitment to change among preschool teachers. The sample in this study were 118 preschool teachers in Buleleng District. The results indicated that there is a significantly positive relationship between learning agility and commitment to change, r (118) = 0.234, p < 0.01. Further results showed that learning agility is also correlated with two dimensions of commitment to change, namely affective commitment to change r (118) = 0.438, p < 0.01 and normative commitment to change r (118) = 0.181, p < 0.05. The results contribute to theoretical advances in understanding learning agility and commitment to change as well as promoting the success of change in early childhood educational institution.